Implementasi Algoritma Adaptive Arithmetic Coding Pada Aplikasi Juz’ Amma Berbasis Android - Ari Maulana Asri; Abdul Sani Sembiring (STMIK Budi Darma, 2021)
The size of the text file is relatively large, where the more information contained in the file, the larger the size of the text file needed to store the information, so that it has an impact on the file size that must be stored on the storage media. The memory size required to store a file is directly proportional to the size of the text file. The problem that occurs is the limited storage space available, especially for Android applications. If the text file size is larger than the storage space or the maximum size limit for a file, sending the text file will fail or the information contained in the text file will not be conveyed properly. This research studies text file compression techniques using arithmetic coding, and implements it for compression and decompression cases. Things to be studied include: looking at the effect of character variations in a text on the compression ratio, the resulting compression time and the decompression time. The experimental results show that the highest compression ratio is obtained when a text has only one type of character. The effect of character variations on the compression ratio is that the more character variations a text has, the lower the compression ratio.